2003
DOI: 10.1577/h02-022
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Antigen Prevalences ofRenibacterium salmoninarum(Rs) Detected by Enzyme-Linked Immunosorbent Assay in Alaskan Pacific Salmon and Trout from 1988 to 2000 and Management of Rs in Hatchery Chinook and Coho Salmon

Abstract: Five species of anadromous Pacific salmon Oncorhynchus spp. and eight species of nonanadromous fish, including trouts Oncorhynchus and Salvelinus spp., Arctic char S. alpinus, and Arctic grayling Thymallus arcticus (collectively called ''trout''), from Alaskan waters were examined by enzyme-linked immunosorbent assay for annual and total prevalences of Renibacterium salmoninarum (Rs) from 1988 to 2000. The total prevalence of Rs antigen was lower among the Pacific salmon and highest among the nonanadromous sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Bacterial kidney disease (BKD) of salmonids is a persistent, often debilitating condition frequently observed among stocks of Chinook salmon, coho salmon, and sockeye salmon of the US Pacific Northwest and Alaska (Meyers et al 2003, Arkoosh et al 2004, Rhodes et al 2006. The enzyme-linked immunosorbent assay (ELISA) has been the diagnostic method of choice in regional hatcheries and captive broodstock programs for nearly 2 decades because of several desirable features.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial kidney disease (BKD) of salmonids is a persistent, often debilitating condition frequently observed among stocks of Chinook salmon, coho salmon, and sockeye salmon of the US Pacific Northwest and Alaska (Meyers et al 2003, Arkoosh et al 2004, Rhodes et al 2006. The enzyme-linked immunosorbent assay (ELISA) has been the diagnostic method of choice in regional hatcheries and captive broodstock programs for nearly 2 decades because of several desirable features.…”
Section: Introductionmentioning
confidence: 99%
“…As previously noted, BCWD outbreaks have occurred at each facility sampled in this study. In general, outbreaks vary in intensity from year to year and facility to facility for F. psychrophilum and for R. salmoninarum (Meyers et al. 2003; Taylor 2004; Madsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) have provided a means to evaluate the prevalence of F. psychrophilum in populations of fish and to determine whether there is a relationship between infection levels in broodstock and BCWD outbreaks in progeny. If a relationship exists, it may be possible to set culling thresholds to control vertical transmission as has been carried out to decrease the incidence of bacterial kidney disease (BKD) (Meyers et al. 2003; Munson, Elliott & Johnson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is also evident that persistence of antigens in kidney tissue makes it impossible to decide, by ELISA results alone, when the fish in question got infected. Persistent antigens could be one of the explanations for the high percentage of positive ELISA readings in kidney samples from groups of wild salmonids in a number of lakes in Iceland (Jónsdóttir et al 1998) and elsewhere (Meyers et al 1993(Meyers et al , 2003. In a recent paper, reporting on a population of wild brown trout, it was shown that 92.9% of fish with positive ELISA in kidney samples tested positive by PCR in at least 1 organ (kidney, spleen, gills mid-gut and oesophagus), although culture was negative (Guðmunds -dóttir et al 2017).…”
Section: Pos In Pcrmentioning
confidence: 99%
“…It is widespread in wild and cultured stocks of salmonids, in fresh and saline water, and is endemic in many parts of the world (Souter et al 1987, Jónsdóttir et al 1998, Meyers et al 2003, Savas et al 2006, Chambers et al 2008. The bacterium can be transmitted horizontally and vertically via the eggs (Evelyn et al 1986) and survive within mononuclear phagocytes (Gutenberger et al 1997).…”
Section: Introductionmentioning
confidence: 99%